ADAPTASI MASYARAKAT PENYINTAS PASCA GEMPA CIANJUR TAHUN 2022 - Fathin Aulia Rahman; Abdul Haris Achadi; Hesti Marlina (Jurnal Manajemen Bencana (JMB), 2023)
The Cianjur earthquake was a large, shallow earthquake caused by the Cimandiri Fault, which was later determined to be the Cugenang Local Fault. The impact of the 5.6-magnitude earthquake devastated most of the Cianjur Regency area, causing a lot of suffering and misery for the post-Cianjur earthquake survivors. Community resilience is needed to face crises and threats of disaster. This research aims to determine the adaptation strategies of community survivors after the Cianjur earthquake disaster. This is quantitative research with a survey method. The research population is based on the sub-district that has the worst impact, namely Cugenang District. The sampling technique uses simple random sampling. Data collection techniques use questionnaires and documentation. The data analysis technique uses quantitative descriptive methods to determine community adaptation strategies. The research results show that the most widely used form of adaptation strategy is the survival strategy, which involves implementing a reduction in the portion of expenditure and control over income and expenditure.